Chlorine tungsten anion and cation co-doped sodium vanadium phosphate positive electrode material and preparation method thereof
Through the chlorotungsten anion and cation co-doping technology and sol-gel preparation method, the rate performance and cycle stability of the cathode material of sodium ion battery are improved, the problem of poor electrochemical performance of existing materials is solved, and higher conductivity and structural stability are achieved.
Patent Information
- Application Number
- CN202411897342.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing sodium ion battery cathode material sodium vanadium phosphate (NVP), has poor electrochemical performance in rate performance and cycle stability, which limits its practical application.
The Na3-xV2-xWx(PO4)3-yCl3y/C structure is formed by using chloro-tungsten anion-cation co-doping technology, and the material's conductivity and structural stability are improved by W4+ ion doping V-position and Cl-ion-doping (PO4)3-position.
It significantly improves the rate performance and cycle stability of the positive electrode material of sodium ion battery, extends the battery life, and improves the conductivity and ion diffusion properties of the material.
Smart Images

Figure CN119725447A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery technology, and specifically relates to a sodium ion battery positive electrode material modified by synergistic doping of anions and cations and a preparation method thereof. Background Art
[0002] At present, fossil energy (including oil, coal and natural gas) is consumed in large quantities. Due to the limited reserves of fossil energy, the growing demand and uncontrolled exploitation will accelerate the depletion of fossil energy. At the same time, environmental problems such as soil pollution and greenhouse effect have also occurred. Therefore, exploring new energy systems has become a top priority. Lithium-ion batteries, as an electrochemical energy storage device, have the advantages of high operating voltage and long cycle life. At present, advanced lithium-ion battery technology has been applied to many mobile electronic devices and electric vehicles. However, due to the relative shortage and uneven distribution of lithium sources and rising prices, the application and development of lithium-ion batteries have been limited. In order to alleviate these problems, many studies have focused on new alternative energy systems. Sodium-ion batteries are considered to be the most suitable alternative to lithium-ion batteries. Sodium-ion batteries have received widespread attention in recent years in the storage and conversion of renewable energy. Compared with commercialized lithium-ion batteries, it has the following characteristics: (1) Similar working principles. During the charge and discharge process of sodium-ion batteries, sodium ions are reversibly inserted / extracted between the cathode and anode, so it is called a "rocking chair" battery. Sodium ions repeatedly migrate between the cathode and anode to achieve energy storage and release. The whole process is very similar to the charging and discharging process of lithium-ion batteries. (2) Sodium and lithium belong to the same main group and have similar chemical and physical properties. Lithium and sodium ions can be reversibly embedded in and extracted from electrode materials with similar structures. (3) Sodium resources are low cost. The reserves of sodium resources on the earth are much higher than those of lithium, and lithium is widely distributed in seawater. Sodium resources are abundant, easy to obtain, and cheap. In this sense, the low-cost characteristics of sodium-ion batteries make them more promising in large-scale energy storage.
[0003] Sodium vanadium phosphate (Na3V2(PO4)3, NVP) is a polyanion compound with a unique three-dimensional NASICON structure that can promote Na + Rapid migration. With its stable structure, high operating voltage and high capacity, it is considered to be the most promising cathode material for sodium ion batteries. + The diffusion capacity is accompanied by a large bulk structure and poor electronic conductivity, resulting in poor electrochemical performance in terms of rate capability and cycle stability, thus hindering its practical application. By carbon coating, sodium vanadium phosphate / carbon composite materials are prepared, the electronic conductivity of the material is improved, thereby improving the electrochemical activity of sodium vanadium phosphate; by doping ions, the structural stability of the material is improved, the ion diffusion channel is expanded, the ion conductivity is improved, and thus the electrochemical performance of the material is improved.
[0004] At present, most of the existing inventions use solid phase method to prepare positive electrode materials, but the material composition prepared by solid phase method is uneven and the particle size distribution is wide. The present invention adopts sol-gel preparation method, which is simple and easy to implement. The sample prepared by this method has a small particle size and good uniformity. In addition, the modification of materials by single element doping is often one-sided. The present invention adopts multi-element doping, which not only improves the conductivity of the material, but also enhances the structural stability of the material and prolongs the battery life. Secondly, cation doping can adjust the lattice lattice constant, stabilize the crystal structure, and slow down the volume change of the lattice during the cycle, but the regulation of the lattice by cation doping is limited, and the lattice stress may not be completely eliminated, while anion and cation co-doping can optimize the lattice structure at a deeper level, reduce the volume expansion amplitude in the cycle, and make the structure more stable. And it can increase the uniformity of the diffusion channel and improve the sodium ion migration performance. Summary of the invention
[0005] The object of the present invention is to provide a chlorine tungsten anion and cation co-doped sodium vanadium phosphate positive electrode material and a preparation method thereof, the method having a simple process. The prepared sodium ion battery positive electrode material has a stable structure, enlarged ion diffusion channels, improved electronic conductivity and ion conductivity, and has good rate performance and cycle stability.
[0006] The present invention first provides a chlorine-tungsten anion-cation co-doped sodium vanadium phosphate positive electrode material, wherein the positive electrode material is W 4+ Ion doping V, Cl - Ion doping (PO4) 3- The chemical formula of the positive electrode material is Na 3-x V 2-x W x (PO4) 3- y Cl 3y / C, where x=0.05, 0.1, 0.15, y=0.09, 0.12, 0.15.
[0007] The present invention also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, which is prepared by a sol-gel method and comprises the following steps:
[0008] (1) Weighing a sodium source, a vanadium source, a tungsten source, a phosphorus source, a chlorine source, and a carbon source according to a molar ratio, pouring them into 60 ml of a deionized water solution, and stirring them in a 50° C. oil bath for 2-4 hours. When the solution turns blue, the temperature is raised to 90° C. and the heating is continued until the deionized water is completely evaporated to form a gel-like substance;
[0009] (2) placing the gel-like substance formed in step (1) in a drying oven for drying to form a precursor;
[0010] (3) The precursor formed in step (2) is ground in an agate mortar, and then placed in a tubular furnace and calcined under an inert atmosphere to obtain a positive electrode material for a sodium ion battery.
[0011] The sodium source is one or more of sodium carbonate, sodium nitrate, sodium acetate, and sodium hydroxide; the vanadium source is ammonium metavanadate; the tungsten source is tungsten disulfide; the phosphorus source is one or two of diammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; the chlorine source is sodium chloride; and the carbon source is one or more of sucrose, glucose, and citric acid monohydrate;
[0012] As a further solution of the present invention: the drying temperature in step (2) is 100°C-180°C.
[0013] As a further solution of the present invention: the high temperature calcination experimental conditions in step (3) are: pre-sintering at 350°C for 3h, and then final sintering at 800°C for 8h, the heating rate is 3-6°C / min, and the inert atmosphere is nitrogen or argon.
[0014] The present invention also provides a method for preparing a positive electrode sheet of sodium vanadium phosphate co-doped with tungsten chloride anions and cations, the steps of which include:
[0015] (1) Grinding the active positive electrode material, conductive additive and binder in a mass ratio of 7:2:1;
[0016] (2) adding an appropriate amount of N-methylpyrrolidone to the powder in step (1), and stirring on a magnetic stirrer for 0.5-8 h to obtain a slurry;
[0017] (3) The slurry is evenly coated on the aluminum foil with a coater, with a thickness of 100-400 μm;
[0018] (4) Drying in a vacuum drying oven at 80-120°C for 8-12 hours;
[0019] (5) Cut the electrode into discs to obtain the positive electrode of the battery.
[0020] Application of the positive electrode material in sodium ion batteries.
[0021] The beneficial effects of the present invention are embodied in:
[0022] (1) Citric acid monohydrate acts as both a chelating agent and a reducing agent, and part of it participates in the reduction reaction, making V 5+ Restore to V 3+ The rest of the carbon source forms a conductive carbon layer on the surface of the material, which improves the conductivity of the material and thus improves the electrochemical performance of the material. The modified material has good rate performance and cycle stability.
[0023] (2) Chloride ions have a large radius, and when doped into the structure of sodium vanadium phosphate, they will cause lattice expansion, which will appropriately increase the lattice parameters of the crystal. Lattice expansion can increase the size of the migration channel for sodium ions, thereby reducing the diffusion energy barrier of sodium ions and increasing the diffusion coefficient of sodium ions in the crystal. 4+ It is a variable valence ion that can participate in redox reactions. 4+ After that, a mixed valence state will be formed in the crystal, and the electronic conductivity will be enhanced through the charge transfer process. The improvement of conductivity helps to reduce the polarization effect of the electrode and improve the charge and discharge efficiency and rate performance. 4+ It can reduce local defects in the crystal, optimize the structural stability of the crystal during the charge and discharge process, and extend the cycle life of the electrode material.
[0024] (3) The particle size of the material prepared by the present invention is reduced, the agglomeration phenomenon is reduced, and the specific surface area of the material is increased, which is conducive to better wetting of the electrolyte and improves the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The X-ray diffraction (XRD) pattern of the sodium ion battery positive electrode material obtained in Example 2 of the present invention;
[0026] Figure 2 This is a scanning electron microscope (SEM) morphology image of the sodium ion battery positive electrode material obtained in Example 2 of the present invention;
[0027] Figure 3 This is a comparison chart of the cycle performance of the target product obtained in Example 2 of the present invention and in Comparative Example 1 after 200 cycles at a 1C rate;
[0028] Figure 4 The figure is a comparison chart of the cycle performance of the target product obtained in Example 2 of the present invention and in Comparative Example 1 after 500 cycles at a 5C rate. Specific implementation methods
[0030] In order to make the technical method of the embodiment of the present invention clearer, the technical method of the embodiment will be clearly described below. The described embodiment is only a part of the embodiment of the present invention, not all of the embodiments, and the protection scope of the present invention is not limited by the following embodiments.
[0031] Embodiment 1:
[0032] Step 1: Preparation of Na by sol-gel method 2.95 V 1.95 W 0.05 (PO4) 2.96 Cl 0.12 / C positive electrode material
[0033] (1) According to the molar ratio, 0.570 g of ammonium metavanadate, 1.05 g of citric acid monohydrate, 0.851 g of ammonium dihydrogen phosphate, 0.963 g of sodium acetate, 0.018 g of sodium chloride, and 0.031 g of tungsten disulfide were weighed and added to 60 ml of deionized water in sequence. The mixture was stirred in an oil bath at 50° C. for 2-3 hours. After the solution turned blue, the temperature was adjusted to 90° C. and stirring was continued until the solution turned into a blue gel.
[0034] (2) drying the gel-like substance formed in step (1) in a drying oven at 120° C. to form a precursor;
[0035] (3) The precursor formed in step (2) was ground in an agate mortar and transferred to a crucible, which was then placed in a tube furnace and sintered in an argon atmosphere, first at 350°C for 3 h, then at 800°C for 8 h, with a heating rate of 5°C min -1 After cooling naturally to room temperature, take out the battery positive electrode material;
[0036] Step 2: Preparation of Na 2.95 V 1.95 W 0.05 (PO4) 2.96 Cl 0.12 / C positive electrode
[0037] (1) The positive electrode material prepared above was mixed with Super P and polyvinylidene fluoride in a mass ratio of 7:2:1, hand-grinded until the mixture was uniformly mixed, and an appropriate amount of N-methylpyrrolidone was added. The mixture was placed on a magnetic stirrer and stirred for 30 minutes to form a slurry. The slurry was coated on an aluminum foil with a thickness of 100 μm, and then placed in a vacuum drying oven at 120° C. and dried for 12 hours to obtain a pole piece;
[0038] (2) 2032 button cells were assembled using metallic sodium as the negative electrode. The entire assembly process was carried out in a glove box filled with argon. The assembly order was: negative electrode shell, metallic sodium, glass fiber separator (GF / D), electrolyte (1M NaClO4 in EC:DC=1:1 vol%), positive electrode sheet (14 mm), gasket, elastic ring, positive electrode shell; the charge and discharge cycle test was carried out in the Wuhan Blue Electric Battery Test System at 5C (1C=117.6 mA g -1 ) current density and in the voltage range of 2.3-4.2 V, the capacity retention rate was 82% after 500 cycles.
[0039] Comparative Example 1:
[0040] The preparation process of the sodium ion battery positive electrode material with the molecular formula Na3V2(PO4)3 / C is exactly the same as that in Example 1, and the preparation process of the pole piece and the battery assembly and testing process are the same as those in Example 1.
[0041] Embodiment 2:
[0042] Step 1: Preparation of Na by sol-gel method 2.9 V 1.9 W 0.1 (PO4) 2.96 Cl 0.12 / C positive electrode material
[0043] (1) Weigh 0.556 g of ammonium metavanadate, 1.05 g of citric acid monohydrate, 0.851 g of ammonium dihydrogen phosphate, 0.987 g of sodium acetate, 0.018 g of sodium chloride, and 0.062 g of tungsten disulfide according to the molar ratio, add them to 60 ml of deionized water in sequence, and stir in an oil bath at 50° C. for 2-3 hours. After the solution turns blue, adjust the temperature to 90° C. and continue stirring until the solution turns into a blue gel.
[0044] (2) drying the gel-like substance formed in step (1) in a drying oven at 120° C. to form a precursor;
[0045] (3) The precursor formed in step (2) was ground in an agate mortar and transferred to a crucible, which was then placed in a tube furnace and sintered in an argon atmosphere, first at 350°C for 3 h, then at 800°C for 8 h, with a heating rate of 5°C min -1 After cooling naturally to room temperature, take out the battery positive electrode material;
[0046] Step 2: Preparation of Na 2.9 V 1.9 W 0.1 (PO4) 2.96 Cl 0.12 / C positive electrode sheet, the preparation process is the same as that of Example 1. The charge and discharge cycle test was carried out in the Wuhan Blue Electric Battery Test System.
[0047] Figure 1 This is the XRD image of the target product obtained in Example 2. As can be seen from the figure, the XRD results show that all characteristic peaks indicate the R-3C space group, which is consistent with the NVP characteristic structure. It can be considered that the introduction of elements will not destroy its crystal composition.
[0048] Figure 2 This is the SEM image of the target product obtained in Example 2. The sample particle size is small, which is conducive to the penetration of the electrolyte.
[0049] Figure 3 The positive electrode material described in Example 2 is 1C (1C = 117.6 mA g -1 ) The cycle stability curve of 200 cycles under the current density. It can be seen from the figure that this material has a high discharge specific capacity of 98.1mAg when applied to sodium ion batteries -1, after 200 cycles, it can still reach 89.5mAg -1 , the capacity retention rate is as high as 91.2%.
[0050] Figure 4 The positive electrode material described in Example 2 is 5C (1C = 117.6mAg -1 ) current density and in the voltage range of 2.3-4.2V, the cycle stability curve after 500 cycles, the capacity retention rate after 500 cycles is 93.1%. This is because the incorporation of anions and cations expands the ion diffusion path and reduces the particle size, increases the specific surface area, improves the electronic conductivity, improves the electrochemical performance of the material, and improves the cycle stability.
[0051] Embodiment 3:
[0052] Step 1: Preparation of Na by sol-gel method 2.85 V 1.85 W 0.15 (PO4) 2.96 Cl 0.12 / C positive electrode material
[0053] (1) According to the molar ratio, weigh 0.541 g of ammonium metavanadate, 1.05 g of citric acid monohydrate, 0.851 g of ammonium dihydrogen phosphate, 0.929 g of sodium acetate, 0.018 g of sodium chloride, and tungsten disulfide.
[0054] 0.093g was added into 60ml deionized water in sequence and stirred in an oil bath at 50°C for 2-3 hours. After the solution turned blue, the temperature was adjusted to 90°C and stirring was continued until the solution turned into a blue gel.
[0055] (2) drying the gel-like substance formed in step (1) in a drying oven at 120° C. to form a precursor;
[0056] (3) The precursor formed in step (2) was ground in an agate mortar and transferred to a crucible, which was then placed in a tube furnace and sintered in an argon atmosphere, first at 350°C for 3 h, then at 800°C for 8 h, with a heating rate of 5°C min -1 After cooling naturally to room temperature, take out the battery positive electrode material;
[0057] Step 2: Preparation of Na 2.85 V 1.85 W 0.15 (PO4) 2.96 Cl 0.12 / C positive electrode sheet, the preparation process is the same as Example 1. The charge and discharge cycle test was carried out in the Wuhan Blue Electric Battery Test System at 5C (1C = 117.6mAg -1) current density and in the voltage range of 2.3-4.2 V, the capacity retention rate was 85.3% after 200 cycles.
Claims
1. A tungsten chloride anion and cation co-doped sodium vanadium phosphate positive electrode material, characterized in that: The chlorine tungsten anion and cation co-doped sodium vanadium phosphate electrode material is composed of W 4+ Ion doping V, Cl - Ion doping (PO4) 3- The chemical formula of the positive electrode material is Na 3-x V 2-x W x (PO4) 3-y Cl 3y / C, where x=0.05, 0.1, 0.15, y=0.09, 0.12, 0.
15.
2. The method for preparing a tungsten chloride anion and cation co-doped sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: The preparation is carried out by a sol-gel method, comprising the following steps: (1) Weighing a sodium source, a vanadium source, a tungsten source, a phosphorus source, a chlorine source, and a carbon source according to a molar ratio, pouring them into 60 ml of a deionized water solution, and stirring them in a 50° C. oil bath for 2-4 hours. When the solution turns blue, the temperature is raised to 90° C. and the heating is continued until the deionized water is completely evaporated to form a gel-like substance; (2) placing the gel-like substance formed in step (1) in a drying oven for drying to form a precursor; (3) The precursor formed in step (2) is ground in an agate mortar, and then placed in a tubular furnace and calcined under an inert atmosphere to obtain a positive electrode material for a sodium ion battery.
3. The preparation method according to claim 2, characterized in that: The sodium source in step (1) is one or more of sodium carbonate, sodium nitrate, sodium acetate and sodium hydroxide; The vanadium source is ammonium metavanadate; The tungsten source is tungsten disulfide; The phosphorus source is one or two of diammonium phosphate, diammonium hydrogen phosphate and ammonium phosphate; The chlorine source is sodium chloride; The carbon source is one or more of sucrose, glucose and citric acid monohydrate.
4. The preparation method according to claim 2, characterized in that: The drying temperature in step (2) is 100°C-180°C.
5. The preparation method according to claim 2, characterized in that: The high temperature calcination experimental conditions in step (3) are: pre-sintering at 350°C for 3h, and then final sintering at 800°C for 8h, with a heating rate of 3-6°C / min, and the inert atmosphere is nitrogen or argon.
6. A preparation method for a sodium vanadium phosphate positive electrode sheet co-doped with tungsten chloride anions and cations, characterized by comprising the following steps: (1) Grinding the active positive electrode material, conductive additive and binder in a mass ratio of 7:2:1; (2) adding an appropriate amount of N-methylpyrrolidone to the powder in step (1), and stirring on a magnetic stirrer for 0.5-8 h to obtain a slurry; (3) The slurry is evenly coated on the aluminum foil with a coater, with a thickness of 100-400 μm; (4) Drying in a vacuum drying oven at 80-120°C for 8-12 hours; (5) Cut the electrode into discs to obtain the positive electrode of the battery.
7. The preparation method according to claim 6, characterized in that: The binder in step (1) is one or more of polyvinylidene fluoride or polyacrylic acid, sodium carboxymethyl cellulose, and sodium alginate, and the conductive agent is one or more of Super P, carbon black, and Ketjen black.
8. Use of the positive electrode material according to claim 1 in a sodium ion battery.
Citation Information
Patent Citations
Material with mixture of ions with sodium vanadium phosphate cathode material coated by carbon and preparing method thereof
CN106328911A
Potassium-lanthanum-silicon ternary co-doped sodium vanadium phosphate electrode material as well as preparation method and application thereof
CN113659146A
Sodium vanadium oxychloride phosphate positive electrode material, preparation method and sodium ion battery
CN113745507A
Polyanionic positive electrode material as well as preparation method and application thereof
CN114256446A
Potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate positive electrode material and preparation method thereof
CN119153662A
Cited By
W-doped modified sodium vanadium fluorophosphate positive electrode material and preparation method thereof
CN121044562A